Home garden interventions in crisis and emergency settings - Baliki, Ghassan; Weiffen, Dorothee; Moiles, Gwendolyn; Brück, Tilman (Frontiers in Sustainable Food Systems, 2023)
Homes gardens are a key source of food security and micronutrient-rich fruits and vegetables and are promoted by aid organisations to help households cope in humanitarian emergencies. However, there is a strong divide between the popularity of home gardens among practitioners and the academic evidence of its nutritional, economic, social and political outcomes. This review provides a comprehensive summary of the evidence about home gardens interventions in crisis settings using a three-pronged approach, triangulating evidence from academic literature, expert discussion (world cafe) and a practitioner survey. Our findings show a significant gap between existing research evidence on one hand, and the needs and current practices on the other, particularly where theories and impact pathways of home garden interventions might not hold in crises-affected settings.